Influence management and disturbances on the regeneration of forest stands - Gonçalves, Ana Cristina; Fonseca, Teresa Fidalgo (Frontiers in Forests and Global Change, 2023)
The renewal and sustainability of the forest stands is attained with regeneration. There are three basic methods to regenerate high forest stands: natural regeneration, direct seeding and planting. This study reviews the factors affecting regeneration, the three methods of regeneration and the effect of stand structure on regeneration. Overall, regeneration success can be quite variable whether due to edaphic and climatic conditions, seed loses and seedling mortality. The silvicultural system is relevant to the choice of the regeneration method; selection and irregular shelterwood systems enable using natural regeneration whereas for uniform shelterwood and clear-cut systems direct seeding and planting are better suited. In the former stand stocking management is of primordial role to regeneration success while for the latter are the species selection, seed predators and spontaneous vegetation control.